Microbiological evaluation of food manipulator’s hands and nasal cavity in a food unit of a university hospital - Machado, Juliana R.; Marson, Jorge M.; Oliveira, Ana C. S.; Silva, Paulo R.; Terra, Ana P. S. (Medicina (Ribeirao Preto), 2009)
This work had as objectives identify microorganisms present in the hands and nasal cavity of food handlers that work in a kitchen of a University Hospital. It was collected samples of 24 individuals usingswab Staphylococcus aureus , with 41.67% harbouring this bacterium in nasal cavity, 41.67% in the palm of the hand, and 16.67% in both hands and nasal cavity. Another microorganism detected was Escherichia coli , present in 29.17% of handlers, being 28.57% in nasal cavity and 71.43% in the hands of manipulators. In 12.5% of food handlers were found both S. aureus and E. coli in their hands. The demonstrations of S. aureus e E. coli in the food handlers´ isolated samples indicate food contamination; arise from contaminated hands and nasal cavity of them. The prevention for this contamination can be applied adopting an orientation procedure and available of products that facilitate the right sanitation of the hands in the work environment. s soaked in saline solution. These samples were sown in culture medium for isolation and identification of the microorganisms. All 24 food handlers presented